Analisis Kinerja Keuangan Dan Pengaruhnya Terhadap Return Saham Dengan Metode Economic Value Added (EVA), Market Value Added (MVA), Dan Cash Value Added (CVA) (Studi Kasus Pada Sektor Transportasi dan Logistik Tahun 2019-2022) - Nicho Wahyu Andriawan; Mohammad Rizal; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine the influence of financial performance explained through Economic Value Added, Market Value Added, and Cash Value Added variables on Stock Return. This research falls under Explanatory Research, employing a quantitative method. The population of this study consists of all companies in the Transportation and Logistics sector listed on the Indonesia Stock Exchange (BEI) during the period 2019-2022. The sampling technique used is purposive sampling with 15 companies, resulting in 60 observations for the study. However, during the normality test, there were 8 observations that had significantly different values from the other observations (outliers). Therefore, this study uses 52 observations. The data used in this research is secondary data accessed through the official website of the Indonesia Stock Exchange. Data analysis was conducted using SPSS 29.0, with the aim of testing the influence of Economic Value Added (X1), Market Value Added (X2), and Cash Value Added (X3) on Stock Return (Y). The results of this study indicate that Economic Value Added, Market Value Added, and Cash Value Added have positive and significant effects on Stock Return. Keywords : Economic Value Added, Market Value Added, Cash Value Added, Stock Return.